Orthographic influence on English word recognition by Spanish and Korean learners - Maria Teresa Martinez Garcia (Estudios de Fonética Experimental)
This study explores how visual-orthographic information influences the perception and recognition of phonemes in a second language (L2). Spanish and Korean learners of English participated in tasks focusing on the English labiodental /v/ and bilabial /b/ phonemes, which are either allophonic or non-existent in their native languages but phonemic in English. The findings demonstrate that the participants’ first language (L1) significantly impacts their ability to perceive and recognize these English phonemes. Additionally, orthographic cues were found to play a crucial role in this process. The results support models that emphasize the importance of L1-L2 phoneme mapping and highlight the influence of orthographic information in L2 word recognition.